Varietal screening of sesamum (Sesamum indicum L.) under organic management in mid hills of Sikkim - Singh, Raghavendra; Avasthe, R.K.; Babu, Subhash; Singh, Abhishek; Sharma, Puscal; Vrushali, Vrushali; Qureshi, Md. A. Aziz (Indian Journal of Hill Farming, 2019)
A field experiment was undertaken to evaluate the yield potential of sesamum varieties under organic management at the Research Farm, ICAR-National Organic Farming Research Institute, Tadong, Sikkim in the pre-kharif season (Feb-March) of 2017. Six sesamum varieties e.g., TKG-308, Sabatri, GT-10, Prachi, Amrit and TRC-Til were laid out in a randomized complete block design and replicated thrice. The results indicated a significant variation among the varieties in growth and seed yield parameters. Among the varieties, GT- 10 produced tallest plants (95.57 cm) and the smallest was in TRC-Til (74.80 cm). The varieties GT-10 and Prachi matured early and took 149 days for maturity. Sesamum variety Sabatri produced the maximum number of capsules per plant (54.6) while minimum number of capsules per plant (16.0) by TKG-308. Among the varieties, significantly higher seed yieldwas observed in GT-10 (7.6 q/ha) and TKG-308 (6.5 q/ha) over others.